Respostas
respondido por:
0
Achando o último termo ou 15º termo:
an = a1 + (n-1) r
an = 8 + (15 - 1)5
an+ 8 + 14.5
an= 8 + 70
an= 78
Achando a soma dos termos:
Sn = [(a1 + an)n] : 2
Sn = [(8 + 78)15]: 2
Sn = [86 . 15] : 2
Sn= 1290 : 2
Sn = 645
an = a1 + (n-1) r
an = 8 + (15 - 1)5
an+ 8 + 14.5
an= 8 + 70
an= 78
Achando a soma dos termos:
Sn = [(a1 + an)n] : 2
Sn = [(8 + 78)15]: 2
Sn = [86 . 15] : 2
Sn= 1290 : 2
Sn = 645
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás